Biocontrol of snail-borne parasites with the glossiphoniid leech, Helobdella austinensis - Saglam, Naim; Melissaratos, Diana S. S.; Shain, Daniel H. H. (Royal Soc, 2023)
Parasites in which freshwater snails are intermediate hosts pose a serious threat to human health worldwide. We show here that freshwater snails can potentially be controlled by leech predation; in principle, this approach could significantly reduce snail-borne parasitic diseases (SBPDs). Specifically, glossiphoniid leeches, Helobdella austinensis and congener species, consume freshwater snails indiscriminately, while other common leeches do not. A single adult H. austenensis, for example, can consume up to its weight in snails, e.g. Physella acuta, per day. Our predator-prey models suggest that snail populations could be eliminated in relatively short time periods (approximately six months) using a leech biocontrol approach. This could have considerable impact on global SBPDs by breaking the intermediate host life cycle.
Keywords: intermediate host; parasitic disease; population dynamics; predator-prey